The first record of Amaurobius C.L. Koch, 1837 (Araneae, Amaurobiidae) from China, with description of two new species - Zhang, Li; Wang, Lu-Yu; Zhang, Zhi-Sheng (Zootaxa, 2018)
Two new species of Amaurobius from China, A. songi sp. nov. and A. spinatus sp. nov. are described on morphological characters of males and females. They are generally very similar to all known Amaurobius species from India, Europe and North America but differ in some details of the copulatory organs. The two species represent the first record of Amaurobius in China.